Some results on cordiality labeling of generalized Jahangir graph - Roslan Hasni; S. Matarneh; Almothana Azaizeh (Indonesian Journal of Combinatorics, 2017)
In this paper we consider the cordiality of a generalized Jahangir graph $J_{n,m}$. We give sufficient condition for $J_{n,m}$ to admit (or not admit) the prime cordial labeling, product cordial labeling and total product cordial labeling.